Perbandingan Pemasaran Produk Sambal Hj. Ani Secara Digital Menggunakan Platform Marketplace Dan Media Sosial - Rumondor, Gabriena Juliana Isabel; Timban, Jean Fanny Junita; Waney , Nordy F.L. (AGRI-SOSIOEKONOMI, 2023)
The research aims to compare the marketing of Sambal Hj.Ani products using marketplace and social media platforms. The research was conducted from December 2021 to April 2022. The data used was digital marketing data for Sambal Hj.Ani obtained through interviews with Sambal Hj.Ani business owners and distributing questionnaires using the Google form to 15 consumers. Analysis of the research data was carried out in a qualitative descriptive manner. The results of research on differences in the marketing of Sambal Hj.Ani products on the marketplace platform have various variations with different wholesale prices and COD payments are available, users can find special prices and coupons, also offer cashback, postage discounts, and vouchers. Compared to marketplaces, social media platforms only offer sambal roa, cakalang chili and squid sambal products at fixed prices but there is no choice of COD payment methods. Sambal Hj.Ani's social media provides more precise, fast and expressive interactive with buyers as well as a neat and attractive display of designs, including contacts and addresses, highlighted with customer testimonials. The marketplace admin only needs to handle complaints, submit orders, and track marketplace inventory. Sales in July-September 2022 through the marketplace sold 210 bottles. In contrast, 56 bottles of the same product were sold via social media channels during the same time period. This shows that more effective marketing efforts lead to an increase in product popularity in the market.